Videos from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 - Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (PANGAEA, 2023)
Videos as recorded by a HD-zoom camera (Bowtech Surveyor WAHD) with a 10:1 optical zoom attached to a remotely operated vehicle (ROV) during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition between November 2019 and September 2020.
Keywords: BEAST; MOSAiC expedition; Remotely operated vehicle (ROV); Sea ice